Multifunctional rural landscape: a systematic review and bibliometric perspective - Shaohua, Liu; Mohd Ali, Noor Azizi; S. Muthuveeran, Adam Aruldewan (Universidade Federal de Mato Grosso, 2024)
This study offers a glimpse into the research direction of “Multifunctional” and “Rural Landscape” by using a bibliometric research approach as well as the VosViewer quantitative analysis software, presenting the knowledge structure of the field with a scientific knowledge map, mainly in the form of information visualization. Based on the quantitative analysis of the bibliographic data, the study reveals three thematic clusters for this research direction in the Web of Science database: first, “ecosystem services” and “management”; second, “multifunctional agriculture,” “land-use”; third, “sustainability,” “diversity.” These three thematic clusters clarify the current state of research on Multifunctional Rural Landscape and provide a reference for subsequent research. The study suggests that future research will be situated in the post-epidemic era and the contemporary context of the fourth industrial revolution, based on its combination of rural landscape with a study on rural landscape perception experience, to form new research themes.